Andina ideology in hispanic family Huánuco organization of the Institute of Public Higher Education Teaching "Marcos Duran Martel" Huánuco - PonceEIngunza, Félix (2019)
Ideology Hispanic Andean, in the organization of the family huanuqueña is a descriptive investigation of mixed approach, which "Marcos Durán Martel" of Huánuco carried out in the Pedagogic Public Institute of Top Education, with the purpose of knowing about what way demonstrates the ideas, traditions, conception of the world and about the life; customs, and the cosmovisión, in the organization of the family. Hispanic Identifies the force of the Andean ideology in the organization of the families huanuqueñas, in the pupils of the Pedagogic Public Institute of Top Education "Marcos Durán Martel" Huánuco. There was used the descriptive method, technology of the survey and the questionnaire as instrument of compilation of information applied to 109 students conformantes of the population and sample. Hispanic identified the force of the Andean ideology in the organization of the family's huanuqueñas, in the pupils of the Top Pedagogic Public Institute "Marcos Durán Martel" Huánuco. The Hispanic ideology is in force in the conscience of the students across the idealistic conception of the world, according to them, God has created the world and to the man and they consider the civil and religious wedding to be important to organize the family. The Andean ideology that consists of the materialistic conception of the world, across the belief of the power of the nature (auquillo, huancas, jirca) is not accepted for the most part by the students, but they recognize of vital importance the participation of the family extended in the organization of the new family; and, finally it was achieved to determine that the family huanuqueña, one organizes under rules and traditional customs.